Exploring the Intersection of Citizenship and Land Tenure A Comprehensive Perspective on Agraria Law - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Fitri Wahyu Anggraini; Della Rahmayani; Robith Thoriq Al-kautsar (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
This study explores the intersection of citizenship and land tenure, examining how legal frameworks influence access to land and impact social identities within agrarian contexts. Employing doctrinal legal research, this research synthesizes literature and analyzes primary legal sources to uncover the principles governing land rights as they relate to citizenship status. The study utilizes a combination of statutory, case, conceptual, historical, and comparative approaches to provide a comprehensive view of land tenure systems across different regions and cultures. Findings indicate that citizenship status significantly affects land ownership and tenure security, often marginalizing certain groups such as women, indigenous communities, and non-citizens. The results underscore the need for legal reforms that recognize equitable land rights and address social disparities within land governance frameworks. This research contributes to the ongoing discourse on agrarian law, advocating for policies that prioritize social justice and inclusivity, thereby enhancing sustainable development and resource management.Keywords: agrarian law, land ownership rights, citizenship dynamics, Indonesian citizens, legal framework.